Partisipasi Masyarakat Desa dalam Upaya Mengembangkan Objek Wisata Goa Tenggar: (Studi Kasus pada Desa Tenggarejo Kecamatan Tanggunggunung Kabupaten Tulungagung) - Jalu Sora Wicitra; Putri Cinta Mei (Universitas Islam Balitar, 2025)
Community participation plays an important role in the development of sustainable tourism. In the concept of good governance, there are 9 principles of good governance indicators, one of which is community participation. This study aims to analyze and describe community participation in the efforts of Tenggarejo Village, Tanggunggunung District, Tulungagung Regency to realize Tenggar Cave as an educational tourism object. The method used in this research is a qualitative method with a descriptive approach. Data collection was carried out using interviews, document studies and observation methods. In-depth interviews were conducted with the Head of Tenggarejo Village, Secretary of Tenggarejo Village and Chairperson of the Tenggarejo Village POKDARWIS. The results showed that community participation in the development of Tenggar Cave as a tourist attraction was carried out in the form of: a) Participation in the planning dialogue for the development of Tenggar Cave as a tourist attraction; b) Participation in implementation by creating and managing social media, organizing events, participating in exhibition events and participating in the Tulungagung Geopark proposal; c) Participation in benefits by getting financial benefits from events held and providing homestays for researchers. The research shows that the degree of community participation in the development of Tenggar Cave as a tourist attraction is at the partnership level, which is indicated by the collaboration between the Tenggarejo Village community through POKDARWIS with the Tenggarejo Village government and the Tulungagung Regency Government. The conclusion of this study is the need for collaboration between the government, the community in designing inclusive programs oriented towards increasing community participation. The recommendation given is through regular dialogue within the Tenggarejo Village POKDARWIS itself, between the community and the Tenggarejo Village government. This is intended so that the community can discuss ideas, suggestions and suggestions. Provide authority in designing, implementing, monitoring and evaluating activities to the community in improving the quality and quantity of organizing events in the Tenggar Cave area to increase benefits for the community around Tenggar Cave. As well as creating special social media accounts related to Tenggar Cave, with the existence of special social media related to Tenggar Cave, it is hoped that it can provide information and promotion related to Tenggar Cave as a tourist attraction.